2022
DOI: 10.1093/nargab/lqac023
|View full text |Cite
|
Sign up to set email alerts
|

scREMOTE: Using multimodal single cell data to predict regulatory gene relationships and to build a computational cell reprogramming model

Abstract: Cell reprogramming offers a potential treatment to many diseases, by regenerating specialized somatic cells. Despite decades of research, discovering the transcription factors that promote cell reprogramming has largely been accomplished through trial and error, a time-consuming and costly method. A computational model for cell reprogramming, however, could guide the hypothesis formulation and experimental validation, to efficiently utilize time and resources. Current methods often cannot account for the heter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…Ψ g and Φ g are two sets of gene-specific, time-invariant parameters, which control the influence of TFs on the target gene, and the shape of target gene’s phase portraits, respectively. Our findings and early studies 37 have shown that it is feasible to infer the regulation relationship according to the learned parameter in linear regression models based on expression data. Additionally, linear models always have high interpretability, and rarely suffer from over-fitting.…”
Section: Methodsmentioning
confidence: 58%
See 1 more Smart Citation
“…Ψ g and Φ g are two sets of gene-specific, time-invariant parameters, which control the influence of TFs on the target gene, and the shape of target gene’s phase portraits, respectively. Our findings and early studies 37 have shown that it is feasible to infer the regulation relationship according to the learned parameter in linear regression models based on expression data. Additionally, linear models always have high interpretability, and rarely suffer from over-fitting.…”
Section: Methodsmentioning
confidence: 58%
“…In TFvelo, the RNA velocity , which is defined as the time derivative of RNA abundance, is determined by the abundance of involved TFs X g and itself, Using a top-down strategy, which can relax the gene dynamics to more flexible profiles 12 , TFvelo directly designs a profile function of target gene’s expression level, where Ψ g and Φ g are two sets of gene-specific time-invariant parameters, which describe the influence of TFs on the target gene, and the shape of phase portraits, respectively. Considering that linear models have been employed to represent the gene regulatory in previous studies 37-39 , is implemented with a linear model . The profile function of y g ( t )1 can be chosen flexibly from a series of second-order differentiable functions 12 , which is designed as a sine function in implementation ( Methods ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, CRE accessibility information combining with motif enrichment analysis is proved capable of identifying potential regulatory pathways to replace ChIP-seq based dataset utilized in the current study. 5 Refining meta-GRN reconstruction method in consideration of having input data from simultaneous scRNA-seq and single cell ATAC-seq (scATAC-seq), such as SHARE-seq published in late 2020, 63 can potentially further improve applicability of AGEAS; however, accessibility of corresponding datasets will be essential for performance assessment and method development. Similarly, initial set of classification models is also subject to change in response to future computational studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, both methods may require large scale of additional background data to be applicable in other studies such as analyzing physiological or pathological development of selected cell type. The scREMOTE 5 published in 2022 is a potential method to extract generalized regulatory elements since limited background data is required with sequencing data representing sample classes. But prior knowledge on key TFs and marker genes is indispensable.…”
Section: Introductionmentioning
confidence: 99%
“…to evaluate various computational methods [39,40]. Due to a large imbalance in cell types of original dataset, we subsampled equal number of each cell type in the hair follicle development system and obtained a dataset of 2,688 cells (Fig.…”
Section: Scdirect Identifies the Tfs Directing Mouse Hair Follicle De...mentioning
confidence: 99%